Penerapan Uji Korelasi Rank Spearman Untuk Mengetahui Hubungan Tingkat Pengetahuan Ibu Terhadap Tindakan Swamedikasi Dalam Penanganan Demam Pada Anak - Dian Mustofani; Hariyani Hariyani (UJMC (Unisda Journal of Mathematics and Computer Science), 2023)
Fever in children is not a disease, but a symptom. To deal with fever in children, appropriate self-medication measures are needed by the mother. Self-medication is an activity of self-medication starting from the selection and use of drugs, both modern, herbal and traditional medicines by an individual to treat a disease or symptoms of a disease. This study will discuss the application of the Spearman Rank correlation test to find out several factors that affect the level of mother's knowledge of self-medication in treating fever in children.